Tanda-Tanda Perundungan dalam Film “Are You Okay?” - Osvaldo, Juan; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
A film is a moving image or so-called audio-visual media. Film can be used as a medium for conveying messages, and films currently act as a popular medium for conveying messages very effectively. Every film is always built with many marks. These signs have the meaning that the filmmaker wants to convey. In this research, the researcher wants to know and describe the signs of bullying in the short film